2016
DOI: 10.1177/1470320316646884
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with irbesatan may improve slit diaphragm alterations in rats with adriamycin-induced nephropathy

Abstract: Objective:The study aimed to evaluate the effects of oral administration of irbesartan in adriamycin-induced nephropathy considering laboratory changes, kidney histology, and expression of proteins related to slit diaphragm and cytoskeleton of the podocyte.Methods:The animals were divided into control, model, methylprednisolone (MP), and irbesartan groups. The 24-hour urinary protein and biochemical indicators were determined, and renal pathological changes were observed. The mRNA and protein expression of nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In addition to the well-known hemodynamic effects of inhibiting the renin-angiotensin-aldosterone system (RAAS) ( 215 ), both angiotensin-converting enzyme inhibitor (ACEI) and AngII type 1 receptor blocker (ARB) have shown to significantly increase nephrin expression in murine diabetic models ( 157 , 216 ). A similar effect was also observed in rats models by adriamycin-induced nephropathy and PAN ( 217 , 218 ). Since AngII has a direct TRPC6-mediated calcium signaling ( 219 , 220 ) which results in ROS expression ( 221 ) and proteinuria ( 222 ), inhibiting TRPC6 indirectly via AngII blockade is a feasible strategy in proteinuric diseases such as FSGS.…”
Section: Introductionsupporting
confidence: 77%
“…In addition to the well-known hemodynamic effects of inhibiting the renin-angiotensin-aldosterone system (RAAS) ( 215 ), both angiotensin-converting enzyme inhibitor (ACEI) and AngII type 1 receptor blocker (ARB) have shown to significantly increase nephrin expression in murine diabetic models ( 157 , 216 ). A similar effect was also observed in rats models by adriamycin-induced nephropathy and PAN ( 217 , 218 ). Since AngII has a direct TRPC6-mediated calcium signaling ( 219 , 220 ) which results in ROS expression ( 221 ) and proteinuria ( 222 ), inhibiting TRPC6 indirectly via AngII blockade is a feasible strategy in proteinuric diseases such as FSGS.…”
Section: Introductionsupporting
confidence: 77%
“…cases, in vitro nephrotoxicity assays are performed by using proximal tubular cells without considering the podocyte that represents, nevertheless, a potential target for drugs. Our model appears to be closed to the functional state of normal human renal cells displaying a selective filtration that could be modulated by nephrotoxic drugs (PAN and ADR) known to induce proteinuria in vivo [16,17]. In addition, the analysis of F-actin distribution and nephrin or ZO-1 expression indicates a good correlation between functional and morphologic events due to treatments with these two drugs.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies showed that a tyrosine residue in the nephrin cytoplasmic region could be phosphorylated by Src family kinase Fyn, resulting in interaction between nephrin and podocin, as well as downstream signal pathway enhancement [ 4 ]. Podocin has a hairpin-like structure and embeds in the membrane, interacts with nephrin and CD2AP via cytoplasmic carboxyl terminus, and then mediates connection between SD and podocyte cytoskeleton to stabilize podocytes[ 5 ]. CD2AP is located on the podocyte cytoplasmic side, it can not only adjust cytoskeleton arrangement by connecting directly with F-actin, but also conduct signal transduction by combining directly with nephrin and podocin.…”
Section: Introductionmentioning
confidence: 99%